IPO Banks Pitch, Selection and Mandate - Espinasse, Philippe; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Former banker Philippe Espinasse, offers advice for the interview, selection and appointment of lead banks, as well as for the execution of an IPO. The book includes case studies from around the world and explains negotiation techniques through which issuers can save considerable time, effort and costs, and also limit their potential liabilities.
Keywords: Capital market; Corporations—Finance.; Investment banking; Securities; Banks and banking; Business enterprises—Finance.; Capital Markets; Corporate Finance; Investments and Securities; Banking; Business Finance